Spanish lessons : film, television, and transmedia in contemporary Spain - Smith, Paul Julian (New York : Berghahn Books, 2017)
Though unjustly neglected by English-language audiences, Spanish film and television not only represent a remarkably influential and vibrant cultural industry; they are also a fertile site of innovation in the production of "transmedia" works that bridge narrative forms. In Spanish Lessons, Paul Julian Smith provides an engaging exploration of visual culture in an era of collapsing genre boundaries, accelerating technological change, and political-economic tumult. Whether generating new insights into the work of key figures like Pedro Almodóvar, comparing media depictions of Spain's economic woes, or giving long-overdue critical attention to quality television series, Smith's book is a consistently lively and accessible cultural investigation.
Introduction: film, television, transmedia -- Film. Spanish cinema of the 1980s -- Madrid de Cine: Spanish film screenings -- Almodóvar's self-fashioning: the economics and aesthetics of post-auteurism -- Television. Media migration and cultural proximity: a specimen season of television drama -- LGBT TV Catalonia -- Televisual properties: the construction bubble in three TV series -- (Re)turn to transmedia. Towards transmedia: past and present of cinema and television in Spain -- A new paradigm for the Spanish audiovisual sector?: quality television/popular cinema -- Crisis fictions: novel, cinema, tv -- Conclusion: the audiovisual field in contemporary Spain.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
JSTOR
Keywords: Motion pictures -- Spain -- History -- 20th century; Motion pictures -- Spain -- History -- 21st century; Television programs -- Spain -- History -- 20th century; Television programs -- Spain -- History -- 21st century; Cinéma -- Espagne -- Histoire -- 20e siècle.; Cinéma -- Espagne -- Histoire -- 21e siècle.; Émissions télévisées -- Espagne -- Histoire -- 20e siècle.; Émissions télévisées -- Espagne -- Histoire -- 21e siècle.; PERFORMING ARTS / Reference; PERFORMING ARTS / Film & Video / History & Criticism; Motion pictures; Television programs; Spain; 1900-2099; History